2009
DOI: 10.1177/0267323108101830
|View full text |Cite
|
Sign up to set email alerts
|

Watching the Detectives

Abstract: ■ Visiting the settings of popular media products has become a growing niche within the tourist market. This article provides a content-based explanation for the popularity of one specific example: the TV detective tour. Three popular television series from different linguistic regions of Europe were analysed, each of which has led to substantial tourist numbers: Inspector Morse (Oxford) , Wallander (Ystad) and Baantjer (Amsterdam). The results show that the tourist attraction of the TV detective programme is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 35 publications
2
7
0
1
Order By: Relevance
“…Since the 1990s, research on tourism induced by audio-visual fiction has demonstrated the relationship between the presence of certain places in films and television series and the increase in the number of visitors to them after screening [15][16][17]. Hence, the academic literature has focused on such varied aspects as its role in the construction of the destination image [7,[18][19][20][21][22] and the motivations for the visit [18,[23][24][25][26], the impact of film tourism on local economies [27][28][29][30], the experiences of film tourists [31][32][33][34][35][36][37][38][39][40][41] and their use from the point of view of marketing the destination [7,15,[42][43][44][45], among others.…”
Section: Film-induced Tourismmentioning
confidence: 99%
“…Since the 1990s, research on tourism induced by audio-visual fiction has demonstrated the relationship between the presence of certain places in films and television series and the increase in the number of visitors to them after screening [15][16][17]. Hence, the academic literature has focused on such varied aspects as its role in the construction of the destination image [7,[18][19][20][21][22] and the motivations for the visit [18,[23][24][25][26], the impact of film tourism on local economies [27][28][29][30], the experiences of film tourists [31][32][33][34][35][36][37][38][39][40][41] and their use from the point of view of marketing the destination [7,15,[42][43][44][45], among others.…”
Section: Film-induced Tourismmentioning
confidence: 99%
“…As the interviewees implicitly note, couleur locale is an important feature in most detective fiction (Reijnders, 2009). The murder changes an ordinary landscape into an active place of imagination, a story that slowly reveals itself.…”
Section: Cultural Repertoiresmentioning
confidence: 99%
“…In and around Ystad there are Wallander town and regional trails, including 'murder walks' whereby tourists can relive story lines and actually walk in the footsteps of their hero, acting out the scripts and plotlines of particular episodes (Reijnders, 2009;www.ystad.se). Partly as a consequence of the success of the Wallander films a regional centre for film production has been established here (Sjöholm and Jönsson, 2009 …”
Section: Innovationmentioning
confidence: 99%